ANALISIS NERACA PASOKAN DAN KEBUTUHANSAPI DAN DAGING SAPI DI JAWA BARAT - Achmad Firman; Mumun M Sulaeman; Linda Herlina; Marina Sulistyati (Universitas Galuh Ciamis, 2018)
Cattle and beef commodities have become a political commodity because the increase in beef prices has been responded significantly by both legislative and executive institutions. West Java became one of the provinces categorized as the area of beef consumption because the needs of cattle and beef cannot be supplied by local cattle in West Java. Lack of beef cattle is supplied from outside the province or abroad. This study aims to see the amount of cattle and beef cattle production to West Java, the number of cattle and beef cattle needs in West Java, as well as the balance between supply and demand of beef and beef cattle in West Java. This research used quantitative method with secondary data as its base of analysis. The results showed that the number of cattle production calculated from the number of cattle population, the production of calf, and the amount of imported cattle from outside the province or abroad. In 2015, the number of West Java cattle population amounted to 425,486 heads, 60,990 calves, and 219,226 heads of imported cattle. The amount of beef cattle production can reach 75,477,941 kg. The total requirement of cattle and beef cattle in West Java was 408,881 heads and 84,733,150 kg. Based on data of supply and requirement of beef cattle could be calculated balance of cattle beef in West Java. The balance of beef cattle in West Java had a deficit meat during 2011-2015. Keywords: Production, Supply, Consumption, Balance, Beef Cattle